Pengaruh Media Kartu Gambar terhadap Kemampuan Menulis Puisi Siswa Kelas IV SDN Sirnagalih - Septianti, Vena; Saleh, Yopa Taufik; Pratiwi, Anggia Suci (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
Learning to write is one of the fundamental aspects in developing language skills. By learning to write effective poetry, students can improve their ability to express ideas better in written form. The use of word card media in learning to write poetry can overcome problems that occur during learning because word card media can increase students’ creativity in writing so that students are able to express their imagination and feelings into poetry. This research uses a quantitative approach with a quasi-experimental design. The population in this study was all 26 class IV students at SDN Sirnagalih. For the research sample, the control group consisted of 13 students, and the experimental group consisted of 13 students. With a sampling technique using simple random sampling. Based on the research results, the data in this study is normally distributed and homogeneous with a data normality significance level of 0.827 > 0.05 and a data homogeneity significance level of 0.846 > 0.05. Hypothesis testing in this research uses the independent sample t-test. Based on the results of the hypothesis test, the significance value obtained was 0.000 < 0.05. So it can be concluded that there is an influence of picture card media on the poetry writing ability of grade IV students at SDN Sirnagalih.